Design and Development of a Letter Management Information System at a Higher Education Institution in the Special Region of Yogyakarta - Nerys Lourensius L Tarigam; Ike Laura Krisna; Yuliansah Yuliansah; Sutirman Sutirman (Jurnal Administrasi Bisnis, 2026)
This study aims to design and develop a letter management information system at a higher education institution in the Special Region of Yogyakarta, known as Campus Y. The institution currently relies on manual procedures for managing incoming and outgoing correspondence, which causes inefficiencies and delays in information flow. Using a Research and Development (R&D) approach, the study applies the ADDIE model and focuses specifically on the analysis and design phases. Data were collected through semi-structured interviews, field observations, and documentation, and were analysed qualitatively. The results of the needs analysis indicate that incoming and outgoing mail is still managed using physical books and disposition sheets, leading to time-consuming processes and dependence on the physical presence of administrators. Although letter drafting utilizes basic digital tools such as Microsoft Word, the institution lacks an integrated archival system. In response, a system flow was designed using flowcharts, covering processes from mail input and disposition to outgoing letter creation, correction, and storage. The system is expected to streamline correspondence workflows, reduce reliance on manual methods, and enhance the efficiency, traceability, and responsiveness of academic administration. This study is limited to the system design stage and recommends further development and evaluation in subsequent phases. Keyword: system information; letter management; research and development